MOLECULAR-BIOCHEMICAL MECHANISMS OF THE GASTROPROTECTIVE ACTION OF ALOE VERA AND ITS INFLUENCE ON OXIDATIVE STATUS, INFLAMMATORY MARKERS AND SECRETORY FUNCTION OF THE STOMACH - Olimova Dildora Ikhtiyorovna (Web of Journals Publishing, 2026)
This paper presents a systems analysis of the molecular and biochemical mechanisms of the gastroprotective action of Aloe vera. The antioxidant, anti-inflammatory, antisecretory, and reparative effects of the plant's biologically active components are examined. The effects of the polysaccharide acemannan, phenolic compounds, and anthraquinones on the NF-κB and Nrf2 signaling pathways, lipid peroxidation processes, prostaglandin production, and the activity of H⁺/K⁺-ATPase in parietal cells are analyzed. Summarized experimental data on the dynamics of biochemical markers of gastric mucosal damage are presented. Aloe vera is shown to reduce malondialdehyde levels, normalize antioxidant enzyme activity, and reduce the expression of proinflammatory cytokines. The results confirm the potential of using Aloe vera-based preparations in the complex therapy of gastritis and peptic ulcer disease.
Keywords: Aloe vera, acemannan, gastroprotection, oxidative stress, NF-κB, Nrf2, prostaglandins, gastric mucosa.